(3bUI GdEjeGf Hjf GdadSaI hGdYde hGdbQBf (B/s - (3GdLSQ,fOjes 1897-1980 ((3WQGHdS, dHfGf (B: s (3fGTQ ZjQeMOO,s)
(3gPG cJGH aj MhGQ Hjf GdadSaI hGdYbjOI hgh bUI WGdH jSei (B((3MjQGf(B) (3WQC Ydjg GdTc aWQO ef LGeYJg aj HjTGQh aCQTOg CHhg Edi GddMhb HTjNg GdehRhf GdPj jbje bQH SeQbfO aj HdOI (B((3NQJfc(B) (3GdJj ajgG ebGe GdEeGe GdHNGQj, adMb HGdTjN hdbjg hTcG Edjg eG jLO aCeQg Cf jTJQj OaJQG jOhf ajg MhGQ GdQMdI GdWhjdI GdJj dG HO efgG ddNQhL ef GdTc ajHOC GdMhGQ aj GdJYQja HGdYde hGdadSaI hGdaQb HjfgeG hGdejJGajRjbjG, Ke jfGbT BQGA GdadGSaI cGdeYde GdChd hajJGZhQ hHGQefjOS hOjebQjWS hadGSaI GdeSdejf cGdaGQGHj hGHf SjfG hGdQGRj, hYbO aUdG Hjf (B"(3OGQhf hGdLSQ(B" (3hJcde aj GdMXhX hGdeUGOaI Ke Jcde aj GdBjGJ GdchfjI (B: (3GdSeGA hGdbWGQg GdEfHjb (B((3GdeGA(B) (3hGdghGA hGdfaS GdHTQjI heSGcf GdLf (B... (3Ke ChUGg hUjJg(B.s
Keywords: (3GdGjeGfs; (3GdbQBf hGdEjeGfs; (3GdEjeGfs -- (3adSaIs